2004
DOI: 10.1097/00054725-200405000-00016
|View full text |Cite
|
Sign up to set email alerts
|

Diffuse Alveolar Hemorrhage After Infliximab Treatment of Crohnʼs Disease

Abstract: Infliximab (Remicade), a chimeric monoclonal antibody to tumor necrosis factor-alpha (anti-TNF-alpha), is being used with increasing frequency in the treatment of Crohn's disease. Infliximab's safety profile to date has been good with reported adverse events being mild to moderate. We report a case of diffuse alveolar hemorrhage after the second infliximab infusion in a patient with Crohn's disease. The mechanism by which infliximab may have caused the observed pulmonary insult remains unknown. Physicians shou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
14
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(15 citation statements)
references
References 12 publications
1
14
0
Order By: Relevance
“…Infliximab has been used for therapy of CD for more than a decade now, and a review of 233 cases treated with anti-TNF alpha therapies showed that cutaneous vasculitis was the most common manifestation, and lung involvement primarily occurred in the form of interstitial lung disease (15). There have been several reports of infectious (16)(17)(18) and non-infectious (6,(19)(20)(21) pulmonary complications in patients with CD while on infliximab therapy. Hypersensitivity vasculitis with leukocytoclastic vasculitis (22,23) due to use of infliximab was unlikely because of lack of cutaneous involvement in our patient.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Infliximab has been used for therapy of CD for more than a decade now, and a review of 233 cases treated with anti-TNF alpha therapies showed that cutaneous vasculitis was the most common manifestation, and lung involvement primarily occurred in the form of interstitial lung disease (15). There have been several reports of infectious (16)(17)(18) and non-infectious (6,(19)(20)(21) pulmonary complications in patients with CD while on infliximab therapy. Hypersensitivity vasculitis with leukocytoclastic vasculitis (22,23) due to use of infliximab was unlikely because of lack of cutaneous involvement in our patient.…”
Section: Discussionmentioning
confidence: 99%
“…Pulmonary involvement in CD can sometimes precede the development of intestinal inflammation (4), or occur during the course of treatment -either as an extra-intestinal manifestation of CD (5), because of secondary infections or as a side effect of the therapy itself (6). Granulomatous inflammation within the airways or lung parenchyma can occur due to CD but can also occur because of several other forms of primary and secondary lung disorders (Table 1).…”
Section: Introductionmentioning
confidence: 99%
“…31 However, there are only a few case reports of noninfectious pulmonary complications due to infliximab use numbering less than 15 patients so far in the literature, especially in IBD patients. Acute respiratory distress syndrome, 32 diffuse alveolar hemorrhage, 33 and BOOP, interstitial pneumonitis 34 have been reported in literature. In a paper by Ostor et al 34 recently which is the largest case series of pulmonary toxicity from infliximab, 3 of the 5 patients were on concomitant azathioprine and 2 were on leflunomide which has also been associated with pulmonary toxicity.…”
Section: Discussionmentioning
confidence: 99%
“…However, DAH with associated capillaritis has been reported following the administration of propylthiouracil [61,62], hydralazine [63] and All-trans-retinoic acid (ATRA) [64]. Other drugs including, gemtuzumab ozogamicin [65] and infliximab [66], have reportedly led to DAH although the mechanisms remain unknown.…”
Section: Drug-induced Capillaritismentioning
confidence: 99%